Religions, Violence, and Interdiciplinary Dialogue - A. Singgih Basuki (UIN Sunan Kalijaga Yogyakarta, 2018)
Religion, as a moral source, a critic and a perpetrator of change, should be able to tame the behavior of its followers to act in a polite, careful, respectful, and wise manner. In fact, not all attitudes and behaviors of the religious people reflect that, instead, they show an opposite attitude of anarchism and violence. By religion, it is expected that human life is better, wiser, more humane, and more responsible. Besides, by the religion, it is also expected that humans can get closer to God of the universe and live in peace. In the context of interreligious relationships, the reality shows leverage differences, not religious equalities. As a result, there are tensions that trigger conflict and violence between religious communities. One possible solution to overcome the violence in religion is to intensify interreligious dialogue.[Agama sebagai sumber moral, sebagai kritik dan sekaligus sebagai pelaku perubahan, seharusnya bisa menjinakkan perilaku umatnya untuk bertindak secara santun, hati-hati, menghormati sesama, bijaksana serta berkeadilan. Pada kenyataannya, tidak semua sikap dan perilaku umat beragama mencerminkan hal tersebut, justru memperlihatkan sikap yang sebaliknya yakni anarkis dan melakukan kekerasan. Dengan agama seharusnya kehidupan manusia menjadi lebih baik, lebih adil, lebih bijaksana, lebih menyayangi sesama, lebih manusiawi, lebih bertanggung jawab. Dengan agama pula manusia bisa mendekatkan diri kepada Tuhan semesta alam dan hidup secara damai. Dalam konteks hubungan antar agama, yang terjadi adalah saling mengungkit perbedaan-perbedaan, bukan persamaan-persamaan agama. Akibatnya timbul ketegangan yang memicu konflik dan kekerasan antar umat beragama. Salah satu solusi mengatasi kekerasan dalam agama adalah dengan mengintensifkan dialog interreligius.]